Comparision the effect of different materials and fabrication techniques of provisional crowns on its fracture strength (In vitro study) - أمين عبدالله; ريمة صقر (Latakia University Journal -Medical Sciences Series, 2023)
Aim: The aim of the study is to evaluate the effect of the fabrication technique and material type on the fracture strength of provisional crowns to determine the best material and the best fabrication technique of provisional crowns that achieves the benefits of using them . Materials and Methods : Using 3D max software a Model of prepared tooth (Upper right incisor) was designed for receving a full-ceramic crown with (1) mm rounded shoulder finish line and convergence angel of (6°) then 20 metal specimens in a form of the previous designed model were printed using a metal printer . Using Exocad software 20 provisional crowns in a form of upper right incisor were designed then using CAD-CAM technique 20 provisional crowns were fabricated and divided into two groups (each group contain 10 provisional crowns) : The first Group : (10) Poly methyl methacrylate (PMMA) provisional crowns in a form of upper right incisor fabricated using milling technique (Shade A1) . The second Group : (10) photopolymer resin provisional crowns in a form of upper right incisor fabricated using 3D printing technique (Shade A2) . Each provisional crown was cemented to its metal model by using non-eugenol temporary cement then all specimens were stored in distilled water at 37°c for 48 hours in an incubator, later all specimens were subjected to 45° load on the incisal-middle thirds junction of the palatal surface under universal testing machine and the maximum load to produce fracture for each specimen was recorded in newton (N) . Results: Significant difference was observed between groups in the fracture strength values at a 95% confidence norm and P-value ˂ 0.05 . The first group specimens (PMMA provisional crowns group fabricated using milling technique) had a higher fracture strength than the second group specimens . Conclusions: It is recommended to fabricate provisional crowns of PMMA material using milling technique to achieve the benefits of using them, superiorly than photopolymer resin material using 3D printing technique .